2019
DOI: 10.1021/acs.analchem.9b02682
|View full text |Cite
|
Sign up to set email alerts
|

MIND: A Double-Linear Model To Accurately Determine Monoisotopic Precursor Mass in High-Resolution Top-Down Proteomics

Abstract: Top-down proteomics approaches are becoming ever more popular, due to the advantages offered by knowledge of the intact protein mass in correctly identifying the various proteoforms that potentially arise due to point mutation, alternative splicing, post-translational modifications, etc. Usually, the average mass is used in this context; however, it is known that this can fluctuate significantly due to both natural and technical causes. Ideally, one would prefer to use the monoisotopic precursor mass, but this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Automation of data analysis with no loss in accuracy is evolving with the recent developments of both open source and commercial software workflows for biopharma applications. 33 Recent advancements in algorithms for data analysis of protein mass spectra aim at more accurate peak assignment (for accurate monoisotopic or average mass calculation) 99 as well as improved deconvolution of complex product ion mass spectra and attempts to perform de novo TD MS sequencing. 100 In principle, TD/MD MS could be integrated into the next generation MAM workflows, which presently employ BU-derived methods.…”
Section: Further Considerations and Outlookmentioning
confidence: 99%
“…Automation of data analysis with no loss in accuracy is evolving with the recent developments of both open source and commercial software workflows for biopharma applications. 33 Recent advancements in algorithms for data analysis of protein mass spectra aim at more accurate peak assignment (for accurate monoisotopic or average mass calculation) 99 as well as improved deconvolution of complex product ion mass spectra and attempts to perform de novo TD MS sequencing. 100 In principle, TD/MD MS could be integrated into the next generation MAM workflows, which presently employ BU-derived methods.…”
Section: Further Considerations and Outlookmentioning
confidence: 99%
“…The first row shows the error between the experimentally determined (intensity-weighted) and the theoretical average mass. Lermyte et al . and Claesen et al have observed that the average mass is less “precise” and less robust to various MS-related errors as a mass metric than, for instance, the most-abundant mass (second row).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the same model can be devised but with a different covariate, for example, the average or most abundant mass of the molecules. Secondly, a model similar in spirit as MIND by Lermyte et al [ 35 ] can be proposed for DNA that predicts the monoisotopic mass based on the partially observed isotope distribution. Thirdly, we can use the model in combination with the fitting procedure of Senko et al [ 36 ] that scales the elemental composition of an average amino acid, denoted as averagine.…”
Section: Discussionmentioning
confidence: 99%